2023
DOI: 10.3389/pore.2023.1610870
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA MYU promotes ovarian cancer cell proliferation by sponging miR-6827-5p and upregulating HMGA1

Abstract: Background: Long non-coding RNAs (lncRNAs) have been confirmed to play vital roles in tumorigenesis. LncRNA MYU has recently been reported as an oncogene in several kinds of tumors. However, MYU’s expression status and potential involvement in ovarian cancer (OC) remain unclear. In this study, we explored the underlying role of MYU in OC.Methods and results: The expression of MYU was upregulated in OC tissues, and MYU’s overexpression was significantly correlated with the FIGO stage and lymphatic metastasis. K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…Other research of HMGA1 shows that HMGA1 has been identified as a target of miR-296-5p, which involves in cell proliferation in colorectal cancer 20 . Additionally, ST8SIA6-AS1 contributes to hepatocellular carcinoma progression by targeting miR-142-3p/HMGA1 axis 21 and long non-coding RNA MYU promotes ovarian cancer cell proliferation by sponging miR-6827-5p and upregulating HMGA1 22 . Interestingly, a recent study focuses on the terms of the deregulation of a putative cis-acting lncRNA in LUAD, and its effect on the oncogene HMGA1 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Other research of HMGA1 shows that HMGA1 has been identified as a target of miR-296-5p, which involves in cell proliferation in colorectal cancer 20 . Additionally, ST8SIA6-AS1 contributes to hepatocellular carcinoma progression by targeting miR-142-3p/HMGA1 axis 21 and long non-coding RNA MYU promotes ovarian cancer cell proliferation by sponging miR-6827-5p and upregulating HMGA1 22 . Interestingly, a recent study focuses on the terms of the deregulation of a putative cis-acting lncRNA in LUAD, and its effect on the oncogene HMGA1 23 .…”
Section: Discussionmentioning
confidence: 99%